Clinical characteristics and management of hospitalized and ambulatory patients with heart failure–results from ESC heart failure long‐term registry–Egyptian cohort. (8th July 2015) - Hassanein, Mahmoud; Abdelhamid, Magdy; Ibrahim, Bassem; Elshazly, Ahmed; Aboleineen, Mohamed Wafaie; Sobhy, Hesham; Nasr, Gamela; Elmesseiry, Fatma; Abdelmoniem, Ahmed; Ashmawy, Medhat; Farag, Nabil; Youssef, Amr; et al.
Abstract: Aims: Our aim is to describe the clinical characteristics and management of patients hospitalized with acute heart failure (HHF) and ambulatory patients with chronic heart failure (CHF) in Egypt and compare them with heart failure (HF) patients from other countries in the European Society of Cardiology‐Heart Failure (ESC‐HF) registry. Methods and results: The ESC‐HF Long‐term Registry is a prospective, multi‐centre, observational study of patients presenting to cardiology centres in member countries of the ESC. From April 2011 to February 2014, a total of 2145 patients with HF were recruited from 20 centres all over Egypt. Of these patients, 1475 (68.8%) were hospitalized with HHF, while 670 (31.2%) had CHF. Less than one‐third (32.1%) of all patients were females. HHF patients {median age of 61 years [interquartile range (IQR), 53–69]} were older than CHF patients [median age of 57 years (IQR, 46‐64)]; P  < 0.0001. They had more diabetes mellitus (45.4% vs. 31.8%; P  < 0.0001). Left ventricular ejection fraction > 45% was present in 22% of HHF vs. 25.6% of CHF ( P  = 0.17). Atrial fibrillation existed in about a quarter of all patients (24.5%). Ischaemic heart disease was the main cause of HF in Egyptian patients. All‐cause in‐hospital mortality was 5%. Egyptian patients presented at a much earlier age than in other regions in the registry. They had more diabetes mellitus. Atrial fibrillation prevalence was remarkably lower. Other co‐morbidities (renal dysfunction, stroke, and peripheral arterial disease) occurred less frequently. Conclusion: Patients in the Egyptian cohort exhibited distinct features from HF patients in other countries in the ESC‐HF Long‐term Registry.